QUAL2E/2K River Water Quality Modeling - Zainudin, Zaki (s.n, 2012)
Water Quality Modeling (WQM) is an integral part of watershed management in Malaysia as well as many other countries in the world. They are employed for various purposes, such as impact assessment due to development, river rehabilitation studies as well as non-point source pollution characterization. This book does not aim to discuss the underlying mathematical formulation of QUAL2E nor QUAL2K as the respective developers have developed sufficient user manual, which deal with these aspects